Anarchisms and Foucault - da Mata, João (História: Questões e Debates, 2019)
In this article, we try to problematize the possible relations between the contributions brought by the French philosopher Michel Foucault and the anarchisms. Attentive to what he called an analytic of power, his studies did not seek to properly create a theory about power, but to seek an understanding of its functioning and its capillarity in social relations. Going beyond the classical reading of power in its repressive aspect, Foucault's analytic has served as a counterpoint to what some researchers point to a contemporary reading of libertarian thought, making it reshape its practices and actions. Contributions that displace the anarchisms of their enlightenment balances, to think practices of freedom in a continuous and incessant agonistic struggle.